The Production of Tv Fiction Adaptations in Spain (1950-2012) (Cinéma & Cie. Film and Media Studies Journal, 2012)
The purpose of this article is to provide an overview of the most significant TV adaptations in Spain from 1956 to 2012. First of all, the following article comprises a brief overview of a number of the most significant fiction adaptations produced by the public television network TVE, rounded out with a more in-depth account of the TV adaptations developed from the 1990s onwards, when a commercial television networks, such as Antena 3 and Tele 5, entered the audiovisual market. Recently, the adaptation of TV series based on foreign programmes has become widespread in Spain. One special category encompasses programmes adapted to the Spanish television market from foreign series formats (US, Latin America and Europe). Television networks and production companies turn to such major television market in order to identify successful series and formats that may be remade into the buyer’s context.